Being caught in the middle of inter-parental conflict: relationship between inter-parental conflict and attitudes towards marriage among male and female adolescents from divorced families - Yaacob, Siti Nor; Fam, Jia Yuin; Mukhtar, Firdaus; Arshat, Zarinah (Canadian Center of Science and Education, 2016)
Children of divorced family are at greater risk to divorce themselves in later years. In an attempt to understand the process of “transmission of divorce” across generations, the current study examined the potential moderation role of gender in the relationship between inter-parental conflict and attitudes towards marriage among adolescents from divorced Muslim family. A total of 341 secondary school students across three states in Malaysia were recruited to participate in the current study. Results of multivariate analysis revealed that being male and exposure to high inter-parental conflict predicted less positive attitudes towards marriage. Gender has no moderating effects in the relationship between inter-parental conflict and attitudes towards marriage. These findings underscore the deleterious effects of inter-parental conflict on adolescents.